Paired denitrifying bioreactors with wide orientation for increased drainage flow capacity. (1st October 2022) - Maxwell, Bryan M.; Cooke, Richard A.; Christianson, Laura E.
Abstract: Denitrifying bioreactors are a conservation drainage practice for reducing nitrate loads in subsurface agricultural drainage. Bioreactor hydraulic capacity is limited by cross-sectional area perpendicular to flow through the woodchip bed, with excess bypass flow untreated. Paired bioreactors with wide orientations were built in 2017 in Illinois, USA, to treat drainage from a relatively large 29 ha field. The paired design consisted of: a larger, Main bioreactor (LWD: 6.1 × 18.3 × 0.9 m) for treating base flow, and 2) a smaller, Booster bioreactor (7.8 × 13.1 × 0.9 m) receiving bypass flow from the Main bioreactor during periods of high flow. Over three years of monitoring, the paired bioreactor captured 84–92% of the annual drainage discharge which demonstrated an expanded cross-sectional area could improve bioreactor flow capture, even for a large drainage area. However, the paired bioreactors removed 6–28% of the annual N load leaving the field (1.8–5.6 kg N ha −1 removed; 52–161 kg N), which was not a notable improvement compared to bioreactors treating smaller drainage areas. The design operated as intended at low annual flow-weighted hydraulic retention times (HRTs) of usually ≤2 h, but these short HRTs ultimately limited bioreactor nitrate removal efficiency. Daily HRTs of <2 h often resulted in nitrate flushing. The Main bioreactor had higher hydraulic loading as intended and was responsible for the majority of flow captured in each year although not always the most nitrate mass removal. The Booster bioreactor provided better nitrate removal than the Main at HRTs of 3.0–11.9 h, possibly due to its drying cycles which may have liberated more available carbon. This new design approach tested at the field-scale illustrated tradeoffs between greater flow capacity (via increased bioreactor width) and longer HRT (via increased length), given a consistent bioreactor surface footprint. Graphical abstract: Image 1 Highlights: A paired bioreactor design was used to treat subsurface drainage from a 29-ha field. Wide orientation (length: width ratio <1) increased flow capacity. The paired bioreactor treated >84% of annual flow over three years. Annual nitrate removal of 6–28% was not better than conventional bioreactors. Low retention time (<2 h) at high flows limited nitrate removal.